The Urban Revolution. - Lefebvre, Henri, 1901-1991 (University of Minnesota Press, 2014)
His recent translations include The Singular Objects of Architecture by Jean Baudrillard and Jean Nouvel (Minnesota, 2002) and Cyberculture by Pierre Lévy (Minnesota, 2001).